Kekerasan Emosional Dalam Keluarga Sebagai Faktor Kecenderungan Kenakalan Remaja (International Forum of Researchers and Lecturers, 2023)
Juvenile delinquency is a very serious matter if it is not taken correctly. Parents play a very important role in delinquency, one of which is the attitude in which parents educate children. Bekasi. This type of research uses a corelational quantitative study method with a non-procontinue sampling technique that is sampling sampling. This study uses Teknik analisis data korelasi Product Moment dengan menggunakan program SPSS v20. For-Windows. As a result of Pearson's emendation, coefficient correlation between juvenile violence and its tendency to juvenile delinquency is r-0.957, with significant 0,000 (p. 0.01), it is evident that there is an extremely strong relationship between emotional violence and the tendency of juvenile delinquency in the cimmuning, bekasi, and violence.